(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the socio-political environment of the period in which Shahab al-Din Abu Hafs Umar Suhrawardi (1145–1234), one of the major representatives of medieval Sufism and the founder of the Suhrawardiyya order, lived and worked. Against the background of the decline of the Abbasid Caliphate in the twelfth and thirteenth centuries, the study analyzes the political instability, dynastic rivalries, and socio-economic crises of Iraq, together with the reform efforts of Caliph al-Nasir. Particular attention is given to Suhrawardi’s role as “Shaykh al-Shuyukh” and political adviser to the caliph, and to his diplomatic missions to the Ayyubids, the Khwarazmshahs, and the Seljuks of Anatolia. The article shows that both Suhrawardi’s religious and Sufi worldview and his political activity were shaped by these conditions and reflect an important stage in the consolidation of the Sufi orders.